The Rights and Duties (Rights and Responsibilities) of Alumni in the Rules and Regulations of the Polish Pontifical College in Rome in 1866 - STĘPIEŃ, MAREK (Prawo Kanoniczne, 2012)
Polish Pontifical College was established in Rome with decree from 9 March 1866 by the Pope Pius IX. In the same year its Regulation which was divided in ten articles was released, approved and printed. The three of them about the recruiting and expelling the alumni as well as about the priestly ordinations. Other articles concerned as follows: the religious observances and practices, studies and the discipline; rules applying to alumni and two additional parts: concerning Recommendations of the way of preserving rules of the College and the formula of an oath for alumni, the students and their rights and duties. Polish youth having the vocation for the priesthood and appropriate attributes and features could be enrolled o the College. The applying candidate for joining the College was obliged to deliver determined records to the rector. Joining the College the candidates took an oath in the Latin expressing their will of preparing and taking the priestly ordination. Students of the College were obliged to pass the two-year course in philosophy, to finish four years of theological studies and in the sequence of three years to pass canonical and secular law. All alumni in the stated time sat an examination in order to get the bachelor's degree and the bachelor's degree in philosophy, theology and the law. Reasons, for which alumni could be removed were listed in Rules from the College. The rector informed seminars about the duties which are connected with taking holy ordinations. The opinions concerning each of the students were prepared in the end of academic years and later were passed on to the cardinal Protector and the diocesan bishops, who were interested in these opinions. Seminars and workers of the College had the right to receive the identical food and the health care. Rules of the regulation of the College included the obligation of the deputes appointed by the cardinal protector of visiting the College not less than one time for fifteen days. Every seminarian during the visit of inspection could present his situation and to turn with a request for help. Students had the similar equipment in their rooms and identical clothes. The rector was authorized to check the correspondence and books of alumni, making the inspection of rooms and of checking whether students posses the forbidden books or the kinds of books which would prevent them from acquiring the knowledge. Rights and duties of seminarians were similar to the rules and regulations being obeyed in the other Roman colleges, particularly at the Papal UrbanoCollege, of which Rules served as the pattern at editing principles written down in Rules and regulations for the Papal Polish College.